CLINICAL CHARACTERISTICS OF PATIENTS WITH SPONTANEOUS CERVICAL ARTERY DISSECTION - THE POLISH REGISTRY FOR FIBROMUSCULAR DYSPLASIA (ARCADIA-POL STUDY). (June 2018) - Talarowska, P.; Warchol-Celinska, E.; Kurkowska-Jastrzebska, I.; Kostera-Pruszczyk, A.; Gasecki, D.; Jozwik-Plebanek, K.; Florczak, E.; Januszewicz, M.; Czlonkowska, A.; Skowronska, M.; Blazejewska-Hyzorek, B.; Swiatlowski, L.; et al.
Abstract: Objective: To assess the clinical characteristics of consecutive patients with spontaneous cervical artery dissection enrolled into ARCADIA-POL study. Design and method: Out of 250 patients enrolled into ARCADIA-POL study since January 2015 (instituted on the basis of Polish-French collaboration) we present 35 consecutive patients with confirmed spontaneous cervical artery dissection which was one of the inclusion criteria to the study. A standardized FMD data form was used for data collection. All patients underwent detailed clinical evaluation including ABPM, biochemical evaluation, biobanking, duplex Doppler of carotid and abdominal arteries and whole body angio-CT. Results: In our analysis we included 35 patients with confirmed spontaneous cervical artery dissection (27F [68.6%], 11 M [31.4%], mean age: 44.6 ± 8.45 years). 23 (65.7%) patients had internal carotid and 10 (28.6%) had vertebral artery dissection. In two patients carotid and vertebral artery dissections coexisted. Fibromuscular dysplasia (FMD) was confirmed in 13 (37.1%) patients – in 8 patients in one and in 5 patients in two vascular beds. Among patients with cervical artery dissection coexisting with FMD, the most frequent localization of FMD lesions were carotid arteries (61.5%) and renal arteries (38.5%). 20 patients out of 35 (57.1%) were hypertensives with the mean office blood pressure values of 128 ± 19/81 ± 11 mmHg and daytime ABPM values of 129 ± 15/83 ± 10 mmHg on the median number of one antihypertensive agent. 7 patients (20%) were smokers. The most frequent clinical symptoms associated with the occurrence of cervical artery dissection in the analyzed group were headaches (68.6% patients), vision disturbances (45.7% patients), Horner's syndrome (40% patients), dizziness (40% patients), eye pain (40% patients), and neck pain (31.4% patients). In 14 patients (40%) cervical artery dissection was associated with ischemic stroke and in 5 patients (14.3%) with transient ischemic attack. There was no associated hemorrhagic brain complications observed. Conclusions: Our data indicate that in patients with spontaneous cervical artery dissection FMD is present in one third of cases. This group is characterized by relatively high prevalence of hypertension and in more than half of the cases spontaneous cervical artery dissection resulted in acute cerebrovascular event or ischemic stroke.